Albuminuria is Associated With Subendocardial Viability Ratio in Chronic Kidney Disease Patients - Robert Ekart; Sebastjan Bevc; Nina Hojs; Maša Knehtl; Benjamin Dvoršak; Radovan Hojs (Karger Publishers, 2015)
Background/Aims: Albuminuria is a well-established marker of subclinical organ damage. Pulse-wave analysis (PWA) employs the technique of applanation tonometry to obtain a peripheral pulse pressure waveform, from which central hemodynamic data are derived by application of the transfer function. Using PWA we can measure the subendocardial viability ratio (SEVR) and ejection duration (ED). SEVR or the Buckberg index is a non-invasive estimate of myocardial workload, oxygen supply and perfusion and a measure of the ability of the arterial system to meet the heart`s energy requirements. ED is the duration of ventricular ejection. The objective of this study was to evaluate the relationship between albuminuria and PWA parameters in chronic kidney disease (CKD) patients. Methods: We studied 86 CKD patients aged 59.8±13.5 years, 56 (65.1%) were male. PWA analysis and 24-hour ambulatory blood pressure (24hABP) monitoring were performed. The following parameters were calculated: (1) aortic augmentation index with and without correction for a heart rate of 75 (Aix and AIx@ HR75), (2) SEVR, calculated as the ratio of the diastolic pressure time index and the systolic pressure time index, (3) ED, (4) estimated central aortic systolic and diastolic pressure and (5) central aortic pulse pressure calculated as the difference between estimated aortic systolic and diastolic BP. Blood samples and urine albumin-to-creatinine ratio (UACR) were analyzed; UACR values were natural log transformed (lnUACR). Results: Using CKD-EPI creatinine-cystatin C formula the eGFR in patients was 7-130 ml/min/1.73m2 (mean 32.6; SD±24.6). We found statistically significant correlation between lnUACR and cystatin C (r=0.308; P=0.004), eGFR (r=-0.219; P=0.04), hemoglobin (r=-0.255; P=0.02), phosphorus (r=0.222; P=0.04), iPTH (r=0.268; P=0.01), SEVR (r=-0.254; P=0.02) and ED (r=0.315; P=0.003). No statistically significant correlations between lnUACR and cardiac biomarkers TnI, NT-proBNP, central aortic BP and 24h ABP values were found. Using multiple regression analysis statistically significant association was found between SEVR as dependent variable and lnUACR (β=-0.223, P=0.039), sex (β=-0.216, P=0.035), and diabetes (β=0.332, P=0.001). Multiple regression analysis with ED as dependent variable has shown statistically significant association with lnUACR (β=0.242, P=0.031) and diabetes (β=-0.275, P=0.01). Patients were stratified into tertiles according to the lnUACR. Statistically significant differences in serum creatinine (P=0.001), cystatin C (P=0.012), hemoglobin (P=0.03), calcium (P=0.036), iPTH (P=0.008), SEVR (P=0.007) and ED (P=0.004) were found between tertiles. In post hoc analysis we found statistically significant differences between first and third tertile in SEVR (P=0.002; 95% CI:10.5-45) and in ED (P=0.001; 95% CI:-6.89-(-1.87)). Conclusions: Nondialysis CKD patients with higher levels of albuminuria have lower SEVR and higher ED and our results have shown the importance of central hemodynamic parameters like are SEVR and ED as a better or earlier noninvasive hemodynamic indexes in these patients.